ENHANCE PROTECTION GROUNDING FAILURE 17 MH SIPANSIHAPORAS HYDROELECTRIC POWER PLANT BASED ON NEW DESIGN NEUTRAL GROUNDING - Victor H Pangaribuan; Adi Sastra Tarigan; Hamdani (Sean Institute, 2022)
Ground failure is one of the conditions in which leakage current occurs between the phase and neutral which can damage the core of the stator. A grounding failure that occurs will cause a very large current so that the damage that will be caused will be very damaging. The need for protection against grounding failure is very much needed, especially in generators with large capacities. In this paper, we will discuss the design of a protection system against grounding failure at the SIPANSIHAPORAS HEPP, with specifications of 17 MW, 11KV. The protection system that will be discussed in this paper is a Neutral Grounding Transformer (NGT). From the results of the study, it was found that the NGT has a capacity of 46.6 KVA (5 minutes rating), 11000/240 V with a secondary resistor of 0.7 , with a current of 211.7 A (5 minutes rating).